Interventions to improve cervical cancer screening uptake amongst young women: A systematic review. (April 2014) - Albrow, Rebecca; Blomberg, Karin; Kitchener, Henry; Brabin, Loretta; Patnick, Julietta; Tishelman, Carol; Törnberg, Sven; Sparén, Pär; Widmark, Catarina
Abstract Objectives. In view of declining screening uptake in young women, this review aims to summarise the available evidence relating to interventions designed to increase cervical screening uptake amongst women aged ≤ 35 years. Methods. Electronic databases were searched and further articles located by manual searches. Study designs employing a valid comparison group and including women aged ≤ 35 years published through 2012 were considered. Data was extracted on the uptake from either screening programme statistics or as reported by the study subjects. A narrative synthesis was undertaken for each category of interventions identified. Results. Ninety-two records were screened with 36 articles retrieved for further assessment. Four studies met the inclusion criteria, two of which evaluated more than one intervention. One of the studies evaluated the use of a modified invitation letter and reported no significant increase in uptake compared to a standard invitation. Three studies investigated the use of a reminder letter, with two reporting a positive effect on screening uptake in women aged 24–34. Three studies were included which supported the use of physician and telephone reminders. One study on HPV self-sampling reported a positive effect when compared with a reminder letter. Conclusions. There is a lack of randomised controlled trials designed to specifically address falling cervical screening uptake in amongst young women. Cervical screening programmes need to look beyond the use of invitation/reminders letters in this group of women to develop interventions which attempt to overcome as many barriers to uptake as possible.